(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is a vast country with huge biological resources. Of the varied resources fresh water bodies contain protein resources in the form of fish. Inland fish culture is carry out in different pockets of the country. Huge water bodies are used to culture fish. Both in the urban and rural settings inland fishery is carried out and involve a good amount of man power. It has a positive effect in the local, state and national economy. Through this paper an attempt has been made to design a model of information system.